Konsep Smart Building Pada Kenyamanan Termal di Laboratorium Teknik - Anastasia Febiyani (Jurnal Teknik Mesin, 2020)
Engineering Laboratory is a place where students can learn the theory and then practicing of machines operate. Teaching room should be made as comfortabel as possible so can improve students. Room condition whereas there are practicum machines makes the room hotter.. Inadequate room capacity makes students uncomfortabel with the conditions of the practicum. The focus in this study is to examine the thermal comfort obtained by students, measurements of temperature and humidity. The method used to calculate the temperature index by calculating the Predicted Mean Vote Index (PMV), Predicted Dissatisfied (PPD), and Heat Stress Index (HSI). Result for This calculation is then used as a reference in the improvement analysis. The results obtained from the PMV calculation are 2.11 PPD 81.67%. This calculation used as a reference in the improvement analysis.